Automated Optical Flow Based Registration for Adaptive Optics Scanning Laser Ophthalmoscope - Yiwei Chen; Yi He; Jing Wang; Wanyue Li; Lina Xing; Feng Gao; Guohua Shi (IEEE Photonics Journal, 2020)
This study presents an automated registration method based on optical flow for an adaptive optics scanning laser ophthalmoscope. The method was designed to align and average images to obtain a higher signal-to-noise ratio image. A correlation based optical flow image registration method, which has large registration degrees of freedom, is adopted as a local registration method. By comparing the images before and after image registration, we show the effectiveness of our method. Furthermore, the advantage of our method, which is the containment of large registration degrees of freedom, is confirmed.